The Strategic Intelligence and Its Impact on Crisis Management - Sadiq Hussin, Azhar; Rashid Mussahib, Mohsen (Journal of Economics and Administrative Sciences, 2024)
The main purpose of this research is to diagnose the role played by strategic intelligence through its five dimensions (foresight, systematic thinking, future vision, motivation, and partnership) in enhancing organizations' crisis management capabilities. The research problem highlights a lack of awareness regarding the importance of utilizing strategic intelligence in addressing crises faced by organizations in practical settings. Therefore, the significance of this research lies in providing a set of mechanisms that contribute to addressing this issue. Additionally, the research aims to achieve several objectives, including diagnosing the application of strategic intelligence and crisis management within the studied organization. to achieve the research objectives, a descriptive analytical approach was used, encompassing both theoretical and applied aspects. A questionnaire was employed as the primary data collection tool, distributed to a purposive sample of 118 employees within the General Traffic Directorate. After statistically processing the data using various central tendency measures (agreement percentage, mean, standard deviation, difference coefficient, and relative importance), as well as correlation and simple linear regression analysis available in the SPSS-V23 statistical software, the research yielded results confirming the significant impact of strategic intelligence in enhancing the capabilities of employees within the General Traffic Directorate to address crises that hinder their ability to carry out assigned activities and tasks.top of Form Paper type Research paper.